Morphometric and phenotypic variation of muscovy ducks (Cairina moschata) in Central Java, Indonesia - SUTOPO SUTOPO; MIRNA ICE RAMANDHANI; FERRI KRISTIO SIANTURI; ASEP SETIAJI (Society for Indonesian Biodiversity, 2025)
Abstract. Sutopo, Ramandhani MI, Sianturi FK, Setiaji A. 2025. Morphometric and phenotypic variation of muscovy ducks (Cairina moschata) in Central Java, Indonesia. Biodiversitas 26: 4267-4273. The muscovy duck (Cairina moschata) is an important part of traditional poultry systems in Central Java, Indonesia. However, the genetic and phenotypic diversity among local varieties remains poorly characterized, limiting efforts in sustainable breeding and conservation. This study aimed to characterize the morphometric and phenotypic variability of three local muscovy duck types (Local, Rambon, and Jumbo) through quantitative and qualitative assessments. A total of 96 adult female ducks were sampled, comprising 36 Local (Demak), 30 Rambon (Kendal), and 30 Jumbo (Temanggung). Morphometric traits measured included maxilla length, neck length, chest circumference, and wing length, among others. Qualitative traits examined included plumage color and body conformation (e.g., caruncle, breast, shank, and abdomen). Data were analyzed using descriptive statistics, discriminant analysis, cluster analysis, and canonical discriminant functions. Jumbo ducks exhibited significantly larger body dimensions compared to the Local and Rambon groups, with an average chest circumference of 34.6±1.8 cm and neck length of 20.4±1.2 cm. Jumbo ducks also showed predominantly white plumage (80%) and pink bills, contrasting with the darker and more variable coloration in Local ducks. Discriminant analysis revealed chest circumference, neck length, and femur length as key variables for group differentiation, achieving 86.67% classification accuracy for Jumbo ducks. Cluster and canonical analyses confirmed the morphological divergence, positioning Rambon ducks as an intermediate group. Substantial morphometric and phenotypic diversity exists among muscovy duck populations in Central Java. Jumbo ducks are morphologically distinct and likely subjected to selection for meat traits. These findings emphasize the importance of conserving local duck genetic resources for future breeding and sustainable production strategies.